Inhibition of Thrombin by Peptides Containing Lysyl-α-Keto Carbonyl Derivatives - Lewis, Sidney D; Ng, Assunta S; Lyle, Elizabeth A; Mellott, Michael J; Appleby, Sandra D; Brady, Stephen F; Stauffer, Kenneth J; Sisko, John T; Mao, Shi-Shan; Veber, Daniel F; Nutt, Ruth F; Lynch, Joseph J; Cook, Jacquelynn J; Gardll, Stephen J; Shafer, Jules A (Thrombosis and Haemostasis, 1995)
Several H-N-Me-D-Phe-Pro-Lysyl-α-keto carbonyl derivatives were shown to be potent thrombin inhibitors (Ki 0.2 to 27 nM). The inhibitory potencies of these compounds toward tissue plasminogen activator, plasmin and factor Xa were minimal; however, substantial cross-reactivity versus trypsin was observed (Ki values from 0.5 to 1500 nM). Inhibition of thrombin by α-keto carbonyl compounds appeared to occur via a one-step reversible reaction. The α-keto carbonyl inhibitors bound thrombin with a second order rate constant (k, 1–4 μM-1s-1) that was 10–100-fold slower than that expected for a diffusion-controlled reaction. Certain α-kelo earbonyl inhibitors were as potent (on a weight basis) as hirudin when evaluated in a rat arterial thrombosis model. The modest oral bioavailability (10–19%) in rats demonstrated for three of the α-keto carbonyl thrombin inhibitors suggests the possibility that α-keto amide containing thrombin inhibitors may have utility as orally-active antithrombotic agents.